Fundos de investimento em ações no Brasil: performance e tamanho fazem diferença ? - Silva, Felipe Augusto Matos (2010)
This article aims to contribute to the mainstream in Asset Pricing Theory, proposing and testing empirically, with pricing exercises and in-sample forecasting, a multifactor linear approach, such that, it is possible to account for the main empirical evidences in a promising Brazilian financial market: stock mutual funds. Following the methodology developed in Fama and French (1992, 1993), we build two factors, mutual funds zero cost equal weighted portfolios, able to accommodate the size and performance effects observed for these assets, which are used in some applications in an extended version of Capital Asset Pricing Model (CAPM), for a panel with 75 stock mutual funds in Brazil, covering the period between 1998:1 and 2008.12. Both effects, which seem to play a relevant role evidenced, when one uses CAPM in order to price big funds with huge relative performance (very high or very low), are partially accommodated when one adds factors, which are significant individually and jointly in almost 50% of funds in question. The main evidences obtained running individual time series regressions are corroborated if one uses the panel technique estimation with random effects, where both factors seem to be indispensable if one intends to better understand the returns of the mutual funds in Brazil.